Recyclable magnetic Fe3O4 supported photocatalyst for the metal-free ATRP. (15th August 2022) - Su, Hui-Ling; Yang, Mei-Mei; Zhao, Li-Min; Yao, Shu-Juan; Geng, Qian-Nan; Wang, Li-Ping; Li, Guang
Graphical abstract: The magnetic Fe3 O4 supported photocatalyst prepared by connecting the cheap and easy organic dye catalyst RB to the magnetic particles (Fe3 O4 @SiO2 -RB). The Fe3 O4 @SiO2 -RB catalyst can be recycled through simple magnetic separation to catalyze polymerization in a controlled manner, and the catalytic activity of the polymerization reactions decreased slightly in turn. Highlights: Fe3 O4 @SiO2 -RB prepared by connecting rhodamine B to the Fe3 O4 nanoparticles. The structure and catalytic activity of the Fe3 O4 @SiO2 -RB were investigated. The Fe3 O4 @SiO2 -RB catalyst can be recycled through simple magnetic separation. Fe3 O4 @SiO2 -RB catalyst can be recovered and reused for the light-induced ATRP. Abstract: Silica layer coated Fe3 O4 magnetic nanoparticles (Fe3 O4 @SiO2 ) were used to support an photocatalyst rhodamine B (RB) (Fe3 O4 @SiO2 -RB) for the metal-free atom transfer radical polymerization (metal-free ATRP) of methyl methacrylate (MMA) for easy separation and recycling of the catalysts. The metal-free ATRP of MMA was carried out under 365 nm UV light using Fe3 O4 @SiO2 -RB as photocatalyst, and ethyl 2-bromoisobutyrate (EBIB) as initiator. The structure of Fe3 O4 @SiO2 -RB was demonstrated by FT-IR, XPS, XRD and TG. The changes of morphology and specific surface area of Fe3 O4 before and after modification were observed by SEM and BET. For the metal-free ATRP reaction, the polymerization process was controllable, the molecular weight was uniform and end of the molecular chain was active. The Fe3 O4 @SiO2 -RB catalyst can be recycled through simple magnetic separation to catalyze polymerization in a controlled manner for three times, and the catalytic activity of the three polymerization reactions decreased slightly in turn. The implementation of this strategy demonstrates that the photoinitiated catalysts can be recovered and reused for subsequent light-induced ATRP.